Phytoremediation of heavy metals by Mariposa Christia vespertilionis from contaminated soils - Abdul Razak, Dewi Kartini (2018)
Phytoremediation is the technique that uses of plants to remediate pollutants from soils and this approach has not been widely practiced in Malaysia. The objectives of this study were: (i) to determine the potential of Mariposa Christia vespertilionis in uptaking heavy metal from contaminated soils and (ii) to evaluate the heavy metals uptake and translocation in plant parts such as roots, stems and leaves. The seedlings of Christia vespertilionis were planted on ten different treatments with four replicates for each treatment namely; T0 (control), T1 (1 kg soil + 100ppm Cu), T2 (1 kg soil + 200ppmCu), T3 (1 kg soil + 300ppm Cu), T4 (1 kg soil + 100ppm Fe), T5 (1 kg soil + 200ppm Fe), T6 (1 kg soil + 300ppm Fe), T7 (1 kg soil + 100ppm Zn), T8 (1 kg soil + 200ppm Zn), and T9 (1 kg soil + 300ppm Zn). pH both of growth media was determined using galss electrode whereas the concentrations of heavy metals consist of Copper (Cu), Iron (Fe) and Zinc (Zn) in the growth media were analyzed using atomic absorption spectrometer (AAS). The results showed the concentration of heavy metals after harvesting in growth media were highest in Fe concentrations than Zn and Cu, from 1742.23 mg/kg to 696.89 mg/kg in, 71.19 mg/kg to 28.48 mg/kg for Zn in T9, and 5.20 mg/kg to 2.08 mg/kg for Cu in T3. The accumulation of heavy metals in the roots, stems and leaves increased with the increasing of concentrations of heavy metals. The most plant parts that storing Cu and Fe concentrations were roots parts at 0.3 mg/kg and 91.49 mg/kg. Zn concentrations stored most in stems parts at 3.98 mg/kg. Christia vespertilionis seems to have high potential to retain high amounts of Cu, Fe and Zn. Christia vespertilionis showed TF values were greater than 1 and BCF value was lower than 1 for all concentrations of heavy metals. This indicates that Christia vespertilionis has potential as a phytoextractor plant.